Creeping fig (Ficus pumila L.) polysaccharides: a review of extraction methods, structural characteristics, biological activities, and emerging applications in medicine - Dan Xie; Wei Chen; Shuo Niu; Yu Sun; He Jiang (Frontiers in Pharmacology, 2026)
Creeping fig ( Ficus pumila L.) is a traditional plant with both edible and medicinal value, and its achenes can spontaneously form gels at room temperature. As important bioactive macromolecules in creeping fig, polysaccharides have attracted increasing attention due to their biological activities and unique gelling properties. However, current studies on creeping fig polysaccharides remain scattered, and there is still a lack of systematic integration of their extraction and purification methods, structural characteristics, biological activities, structure-activity relationships, hydrogel properties and potential applications. This review summarizes recent progress on creeping fig polysaccharides, with particular attention to the relationship between structural characteristics, biological activities and hydrogel properties, as well as the current evidence supporting their potential applications. Existing studies have shown that creeping fig polysaccharides possess multiple biological activities, including hypoglycemic, anti-colitis, anti-obesity, immunomodulatory and anti-cellular senescence activities, among which inflammation regulation and gut microbiota regulation are frequently involved. In terms of structural characteristics, molecular weight, monosaccharide composition, galacturonic acid content, degree of methylesterification and degree of acetylation are important factors affecting their physicochemical properties, biological activities and hydrogel formation. Creeping fig polysaccharides with low-methoxyl pectin characteristics can form calcium-crosslinked hydrogels, showing potential applications in tissue repair, biolubrication and ultrasound-assisted imaging, although these applications still require further experimental validation. This review aims to provide a systematic and critical reference for the further development of creeping fig polysaccharides in functional food, pharmacology and medicine.